Relationship Supervision and Motivation with Nurse Performance in Meeting Patient's Personal Hygiene Needs - Susi Widiawati; Rian Maylina Sari; Winda Kalpataria (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2018)
Abstract Background: personal hygiene is one of the role of nurse in educating health service. It intends to keep patient’s hygiene during treatment. It is supported by supervision and motivation as stated in nurses’ job description. In fact, personal hygiene has not been run properly according standard operating procedure. The purpose of this study was to know the correlation between supervision and motivation with nurses’ performance in giving health service of personal hygiene in inpatient room. Method: This study was a quantitative using cross sectional method. The samples consisted of nurses in surgical inpatient ward. Total sampling was employed; that is, there were 38 nurses taking part in this research. Data were collected through administering questionnaire. Then, univariate and bivariate analysis were used by using statistic chi-square test. Result: univariate statistic test revealed that 22 (57,9%) of respondents had good performance, 26 (68.4%) of respondents confirmed that supervision run well, 24 (63.2%) of respondents stated that they had high motivation in instructing personal hygiene. Bivariate analysis showed that there was a significant correlation between supervision and nurses’ performance (p-value 0.002<0.05) and there was a significant correlation between motivation and nurses’ performance (p-value 0,002 < 0,05). Conclusion: there was a significant correlation between supervision and motivation with nurses’ performance in instructing personal hygiene to patients at surgical inpatient ward of Raden Matther hospital.